Integrating ecology and poverty reduction. The application of ecology in development solutions. - Ingram, J.C.; DeClerck, Fabrice A.J.; Rumbaitis del Rio, Cristina (Springer, 2012)
At the writing of this book, the world is at a critical crossroads. The year 2010 was the United Nations (U.N.) year of biodiversity and the year when the targets of the Convention of Biological Diversity (CBD), which was signed in 2002, were supposed to have been met. The CBD aimed to achieve by 2010 a ?significant reduction of the current rate of biodiversity loss at the global, regional and national levels as a contribution to poverty reduction and to the benefit of all life on Earth.? However, progress remains elusive ? species extinction rates continue to be 1,000 times greater than background rates in the geological record (Secretariat of the CBD 2006; Walpole et al. 2009, 2010; Butchart et al. 2010).